Long-Run Estimates of the Global Informal Economies and New Insights for 152 Countries over 1997 to 2022 Using an Enhanced MIMIC Approach - Alban Asllani; Roberto Dell'Anno; Friedrich Schneider (Institute of Labor Economics (IZA), 2024)
Using an enhanced MIMIC method, this paper presents new and long-run estimates of the Informal Economy (IE) for 152 countries from 1997 to 2022. We address several limitations found in previous estimates of the IE, notably issues surrounding the missing values, time-invariant country characteristics, and calibration issues with exogenous variables. We enhance the MIMIC model by including fixed effects for country-specific characteristics of IE, thereby providing more reliable and long-run estimates. This approach allows us to control for time-invariant effects across countries by incorporating fixed effects through a transformation of observed variables, thereby holding constant both observable causes and unobserved structural factors unique to each country. Our findings show a significant variation in the key drivers of IE between high-income and not-high-income countries, exhibiting distinct causal effects on the IE depending on different economic developments. In terms of normative implications, our results highlight the need for specific and tailored policies in dealing with the formalisation of informal activities in countries with different levels of income.
Keywords: O17; C39; H26; 330; informal economy; shadow economy; Structural Equation Modelling; MIMIC approach